Creating a Community of Inquiry in Online Library Instruction. Issue 1 (2nd January 2017) - Rapchak, Marcia E.
ABSTRACT: According to the Community of Inquiry (CoI) model (Garrison, Anderson, & Archer, 2000 ), an enriching educational experience online in a collaborative learning environment requires three interdependent elements: social presence, teaching presence, and cognitive presence. Social presence provides interaction in the online environment that allows students to feel like they are in a supportive and open environment. Teaching presence refers not just to teacher-student interaction during the lesson or course duration, but also to a teacher's ability to design an effective learning environment. Cognitive presence in the CoI model is knowledge generated from collaborative interaction. This model has been well-studied in the literature, and has been shown to be a meaningful framework for course development. However, more exploration of CoI in relation to library distance instruction is needed. This article describes the Community of Inquiry model and provides information about the three presences and how they can improve online educational environments.